Refining the laparoscopic retroperitoneal lymph node dissection for testicular cancer - Frederico R. Romero; Andrew Wagner; Fabio A. Brito; Michael Muntener; Guilherme C. Lima; Louis R. Kavoussi (International Brazilian Journal of Urology, 2006)
Since its initial description, the laparoscopic retroperitoneal lymph node dissection has evolved considerably, from a purely diagnostic tool performed to stage germ cell testicular cancer to a therapeutic operation that fully duplicates the open technique. Herein, we describe the current technique employed at our institution, along with illustrations of all surgical steps, and delineate the refinements of the technique over time.